1983
DOI: 10.1021/bi00274a037
|View full text |Cite
|
Sign up to set email alerts
|

A stereochemical and positional isotope exchange study of the mechanism of activation of isoleucine by isoleucyl-tRNA synthetase from Escherichia coli

Abstract: Isoleucyl-tRNA synthetase from Escherichia coli catalyzes the activation of [18O2]isoleucine by adenosine 5'-[(R)-alpha-17O]triphosphate with inversion of configuration at phosphorus. Moreover, isoleucyl-tRNA synthetase does not catalyze positional isotope exchange in adenosine 5'-[beta-18O2]triphosphate in the absence of isoleucine or in the presence of the competitive inhibitor isoleucinol, which effectively eliminates the possibility of either adenylyl-enzyme or adenosine metaphosphate intermediates being i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The conditions employed for the desulfurization of (S'P)-[a-1802]dATPaS in [170] water were chosen carefully to minimize depurination due to low pH conditions generated during the course of the reaction. The use of low pH during the reaction, however, is necessary in order to avoid complications caused by the neighboring group participation by the terminal phosphate group during the hydrolysis of the bromothiophosphoryl intermediate at a higher pH Lowe et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The conditions employed for the desulfurization of (S'P)-[a-1802]dATPaS in [170] water were chosen carefully to minimize depurination due to low pH conditions generated during the course of the reaction. The use of low pH during the reaction, however, is necessary in order to avoid complications caused by the neighboring group participation by the terminal phosphate group during the hydrolysis of the bromothiophosphoryl intermediate at a higher pH Lowe et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…(b) Elucidation of the absolute configuration of chiral DPPsE and chiral DPPsC, on the basis of a safe assumption that desulfurization proceeds with inversion of configuration (Connolly et al, 1982;Lowe et al, 1982Lowe et al, , 1983Potter et al, 1983;Sammons & Frey, 1982;Senter et al, 1983), makes it possible to interpret the results of biochemical study by use of chiral thiophospholipids in a stereochemical way. For example, it is now clear that phospholipase A2 is specific to the RP isomer of DPPsC and DPPsE whereas phospholipases C and D are specific to the Sp isomer.…”
Section: Discussionmentioning
confidence: 99%
“…The configuration of chiral DPPsC and chiral DPPsE can therefore be elucidated by conversion to [lsO]DPPE by procedures of known stereochemistry. It has been shown that desulfurization of various nucleoside phosphorothioates in H2180 mediated by bromine, cyanogen bromide, or Nbromosuccinimide proceeds with inversion of configuration at phosphorus (Connolly et al, 1982;Lowe et al, 1982Lowe et al, , 1983Potter et al, 1983;Sammons & Frey, 1982;Senter et al, 1983). Such a reaction can therefore be used to correlate the configuration of chiral thiophospholipids with that of [lsO]- with no detectable products.…”
Section: Conversion Of Dppscmentioning
confidence: 99%
“…Adenosine (R)-5'-[a-170]triphosphate was prepared as described previously [26,27], and was shown to contain 6 atom % l60, 42 atom % 170, and 52 atom % l80 by 31P-NMR spectroscopy and from the known I7O: l80 ratio (1 : 1.223) in the [170]water used in the synthesis; the sample contained 6 % of the (S)-isomer 126, 271. …”
Section: Methodsmentioning
confidence: 99%